A Review of Chemical Variability and Metal Contamination of Herbaceous Plants in Terms of Health Safety—A Case Study of Tanacetum vulgare L. - Anna Turek (Applied Sciences)
The article presents a review of studies on the chemical diversity of essential oils and extracts from Tanacetum vulgare L. under the influence of environmental factors and the bioaccumulation of heavy metals in the plant. These issues are crucial for consumer safety, especially when they concern plants widely used in alternative medicine. Stress factors to which plants are subjected may result in a decrease in their biological activity or toxic effects (as in the case of Tanacetum vulgare L.). The issue is particularly important in the context of increasing environmental pollution, e.g., with heavy metals, and climate change, which is also a stress factor. The presented review clearly shows that detailed research is required both to identify the components of T. vulgare with specific therapeutic potential and to assess their quantitative changes under the influence of a specific stressor. It was found that there is a need to standardize analytical procedures used in research on the bioaccumulation of metals by medicinal plants. The importance of environmental monitoring in herb-growing areas, as an important element of health policy, is also emphasized.